Awareness and utilisation of postnatal care services among antenatal clinic attendees at ahmadu bello university teaching hospital Zaria - John Kingsley C. Nwajagu; Nkeiruka Ameh; Adekunle O Oguntayo (Nigerian Journal of Medicine, 2017)
BACKGROUND: Postnatal period is the period from one hour to six weeks after the birth of an infant. It is a critical period for the woman,her new born and her family on a physiological,emotional and social level especially because 50-70% of all maternal deaths occur during this period. AIM: To identify the determinants of women's utilization of postnatal clinic services (PNCs). METHODS: A descriptive study on 188 eligible antenatal clinic attendees at the Obstetrics and Gynaecology Department of Ahmadu Bello University Teaching Hospital (ABUTH) Shika-Zaria from October to December 2013.Structured questionnaires were used for the study.Approval was obtained from the Ethical committee of the ABUTH, Shika-Zaria.TheSPSS version 16 was used for data analysis and the results was subjected to descriptive analysis. RESULTS: The majority were Hausas. 39.9% had tertiary school education. Majority of them (42%) were multiparous women, 77.7% were aware of the postnatal services they should receive. Previous antenatal clinic (ANC) attendance was 95.1% and 74.4% attended PNC. Educational level affected PNC utilisation, tertiary education (60%),secondary (28%) and primary (5%).Employed respondents had more PNC attendance (84%) than the unemployed (25%). CONCLUSION:The study shows that awareness, education, employment and antenatal clinic attendance are the promoting factors to utilisation of PNC services and the hindering factors to utilisation of PNCs include lack of awareness,distance and lack of transportation,poverty or lack of money.